Analisis Kualitas Pelayanan terhadap Kepuasan Konsumen pada Cafe D’Fresh di Kediri - Lisa Elvaretta Krisdyar; Sasi Utami; Yogi Yunanto (Economic Reviews Journal, 2024)
The era of globalization makes business competition increasingly competitive. Many businesses operating in the field of similar products and services, such as cafes, will continue to develop and create many creative new ideas so that visitors will have a deep impression of the cafe. The aim of this research is to find out whether service quality influences consumer satisfaction at Cafe D'Fresh in Kediri. This type of research uses quantitative methods with 100 respondents by distributing questionnaires via g-form. Based on the results of the tests carried out, the conclusion that can be drawn in this research is H1, namely that service quality influences consumer satisfaction at Cafe D'Fresh. This means that the Service Quality variable (X) has a positive and significant effect on Customer Satisfaction (Y).